Goodnight Darth Vader - Brown, Jeffrey, 1975- (Chronicle Books, 2014)
"In this Episode, the Sith Lord must soothe his rambunctious twins, Luke and Leia, who are not ready to sleep and who insist on a story. As Vader reads, the book looks in on favorite creatures, droids, and characters, such as Yoda, R2-D2, Han Solo, Chewbacca, Darth Maul, Admiral Ackbar, Boba Fett, and many others as they tuck in, yawn, and settle down to dream"--Amazon.com.